Rancang Bangun Sistem Informasi Reservasi dan Administrasi Layanan Jasa Cuci Toren Berbasis Web Menggunakan Model Agile pada Toren Cleaning Indonesia - Nandang Adriansyah; Mulyo Adji Winoto; Muhammad Zidan Deniswara; Maulana Ardhiansyah (PT. Saha Kreasi Indonesia, 2026)
The operational efficiency of sanitation service providers heavily relies on well-structured administrative and scheduling systems. Toren Cleaning Indonesia currently encounters administrative bottlenecks due to the manual recording of customer reservations and technician assignments via instant messaging. This conventional method often results in redundant data entry, missed maintenance schedules, and inefficient financial recapitulations. This research aims to design and develop a web-based reservation and administration information system using the Agile methodology to streamline business processes. Data were collected through direct observation, structured interviews, and literature reviews. The system development utilized PHP, MySQL for database management, and a responsive web framework, executed across three Agile sprints. The resulting system features a loginless booking interface for customers, an integrated administrator dashboard, and an automated 180-day maintenance reminder system. Black-box testing on 16 functional scenarios yielded 100% validity. In conclusion, the implemented system successfully centralizes data, eliminates archiving losses, and enhances customer retention through proactive automated follow-ups.